Effect of Leadership Style, Supervision and Work Discipline on Employee Performance of PT. Mahesa Bahari International - Roiforuasi Simarmata; Ina Namora Putri Siregar; Siti Tasya Aisah Kasli; Fifi Hardiana; Ahmad Husein; Farandy Angesti Chandra (Jurnal Mantik, 2021)
The purpose of the study was to test the influence of Leadership Style, Surveillance and Work Discipline on the Performance of Employees of PT Mahesa International Maritime research Method is a quantitative approach, type of research is descriptive and quantitative nature of this research is descriptive explanatory. Methods of data analysis is multiple linear regression analysis. The population in this research is 128 employees and the sample amounted to 94 employees. Sample collection techniques, namely simple random sampling. The calculation results of testing the hypothesis partially and simultaneous Style of Leadership, Supervision and Discipline of Work has positive and significant effect on Employee Performance of PT Mahesa International Maritime Field.